Social Media Marketing Activity in Healthcare Services: A Systematic Literature Review - Badri, Dwi Septiadi (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This research is aimed at exploring the role of social media as a strategic capability and how this influences marketing performance in healthcare services. Methodology: Through a systematic literature review approach, this research will explore and synthesize the latest relevant literature, forming a strong knowledge base regarding the concept of social media use for marketing in healthcare services. Results: Descriptive analysis based on the Scopus database reveals research trends using keywords (social AND media AND marketing AND healthcare) reached its peak in 2024 with the United States dominating the area of research. Several new viewpoints emerged, including engagement, brand equity, consumer behavior, and other elements. Applications: This research found and filled existing knowledge gaps, especially in the aspect of social media marketing by healthcare services and its impact on consumers and to provide a basis for further research.